Reliability control of final vibration strengthening of part processing in steel balls medium - Tamarkin, M. A.; Tishchenko, E. E.; Gordiyenko, A. V.; Grebenkin, R. V. (Advanced engineering research (Rostov-na-Donu, Russia), 2017)
Introduction. The research results of the vibration part processing in the steel balls medium are provided. Technological capabilities of the treatment are identified. The concept of process reliability is considered. Factors affecting the output parameters of a (process) control object from the point of view of its reliability, and indicators for estimating the process reliability are determined. Materials and Methods. As an object for the reliability research, the vibration finishing-strengthening processing in the steel balls medium is selected. This process can be performed on the part hardening and finishing operations, peening, and coating (galvanic, paint, rubber, adhesive, etc.) preparation of parts. Samples from various materials applied in machine industry and instrument-making are used. Research Results. A set of models for forming process reliability indices that allow providing increase in efficiency and reaching the specified value and stability of quality parameters of the processed part is obtained. Dependences for the determination of arithmetic average surface roughness, hardening depth, deformation ratio, and cutting time, are determined. A set of pilot studies which results confirm adequacy of the theoretical dependences is carried out. Discussions and Conclusions. A set of the obtained models can help to calculate the accuracy factor value at the stage of process design that will allow predicting reliability of the process accepted for production.